Achados dos potenciais evocados auditivos de estado estavel em crianças ouvintes e crianças portadoras de deficiência auditiva neurossensorial - Calil, Daniela Bortoloti (2006)
The Auditory Steady State Response (ASSR) is a technique of objective evaluation of the hearing and can be done using some frequencies in both ears at the same time. The method consists on modulating the amplitude of each stimulation with a different frequency and presenting them simultaneously. Objective: Describe the findings of the ASSR for children with normal hearing and children with sensorineural hearing loss, in the frequencies of 500, 1000, 2000 and 4000 Hz, simultaneously. Method: Fourteen children with normal hearing, aging from 2 to 19 months; and seven children with moderate to profound sensorineural hearing loss, aging from 3 to 35 months were evaluated using ASSR evoked by multiple simultaneous stimuli with frequencies at 500, 1000, 2000 and 4000 Hz and modulation between 77 and 103 Hz in both ears. Results: the threshold response observed ASSR in Children with normal hearing was 6 to 17,2 dBNAcg, there was no significant difference observed between the frequencies. Children with sensorineural hearing loss, the findings of the ASSR showed a strong correlation with the results of the behavior audiometry. Conclusions: The ASSR is capable of showing audiometric status, specifying the degree and configuration of the hearing loss. It is possible to get responses in the ASSR even when the ABR is absent. The technique of the ASSR must be included in the clinical routine of children s hearing thresholds